IMPLEMENTASI PENYELESAIAN HUKUM ATAS EKSEKUSI JAMINAN DALAM PERBANKAN SYARIAH - Abdul Ghoni (Universitas Semarang, 2016)
Phenomenon that happened [at] banking [of] Moslem law during the time sometime not or not yet touched from principles of Moslem law banking, good in context al-bai' (merchant), al-Ijarah (renting), al-Musyarakah (corporation), al-Mudharabah (sharing holder), Ar-Rahn (the mortage), alqard (receivable debt), ad-dhaman and al-kafalah (guarantee and warranty), al-hawalah (evacuation of debt underwriter), but exactly sometime is equal to principle applied by conventional bank. Principle by this Moslem law banking nor far with the fidusia which in this that penghutang (debitur) that is: (1) giving materialism rights; (2) giving rights prioritize to creditor; (3) enabling to giver of guarantee fidusia to remain to master the object of debt guarantee; ( 4) giving rule of law; and (5) easy to executed the. The problem in this research are: (1) how the principles and remedies for the execution of the collateral in Islamic banking; and (2) how the implementation of remedies for the execution of the collateral in Islamic banking? The method used in this research is the method: (1) observation; (2) interview; and (3)documentation. This research target description of about: (1) how principle and solving of law for executing guarantee in Moslem law banking; and (2) how implementation of solving of law for executing guarantee in Moslem law banking. Result obtained that in solving of law for executing guarantee in banking that: (1) that banking of Moslem law in solving of law for executing guarantee use the law fidusia and act to apply the concept going into effect in Moslem law banking. Therefore principle which must be bring back and apply the Islam concept in running Moslem law banking; (2) that implementation during the time felt by debitor refer the system run by a Moslem law banking, debitor exactly its burdenprogressively heavily because of sanction applied by a banking. Therefore, banking of Moslem law have to bring back or run the banking wheel have to relate the concept kemaslahatan, justice, ta'awun.